EGFR gene copy number increase in vulvar carcinomas is linked with poor clinical outcome. Issue 2 (29th November 2011) - Woelber, L; Hess, S; Bohlken, H; Tennstedt, P; Eulenburg, C; Simon, R; Gieseking, F; Jaenicke, F; Mahner, S; Choschzick, M
Abstract : EGFR copy number increases have been frequently reported in cancer including vulvar carcinomas. Co-amplification of cancer genes plays an important role in the development of many tumour types. To better understand the effect of EGFR aberrations on vulvar cancer phenotype and patient prognosis, the authors analysed EGFR copy number changes using fluorescence in situ hybridisation and EGFR expression by immunohistochemistry in a tissue microarray containing 183 squamous cell carcinomas of vulva. Furthermore, the authors analysed the co-amplification frequency of EGFR with HER2, CCND1, MYC and PIK3CA, respectively. EGFR copy number increase was found in 39.3% of the tumours. Seventeen per cent of vulvar carcinomas showed EGFR high polysomy including 9% with amplification of the EGFR gene. Copy number gain of the EGFR locus was associated with non-basaloid phenotype (p=0.03), high-tumour stage (p<0.001), human papillomaviruse negativity of tumours (p=0.04) and the number of lymph node metastases (p=0.02). EGFR protein expression was statistically correlated to EGFR copy number increase (p<0.05). The observed co-amplification rate of EGFR with all four additionally examined oncogenes was much higher than statistically expected. There was a highly significant association between EGFR copy number increase and CCND1 amplifications (p<0.001) as well as the total number of gene amplifications (p=0.04). EGFR copy number gains were significantly related to unfavourable patient outcome in univariate analysis and multivariate Cox regression analysis. In conclusion, EGFR copy number increases are detectable in a substantial proportion of vulvar carcinomas with relationships to advanced tumour stages and the development of lymph node metastases. EGFR copy number aberrations are connected to other gene amplifications and probably define an human papillomaviruses-independent pathway in the development of vulvar carcinomas. These data support the potential utility of EGFR inhibitors as a therapeutic alternative in a subset of vulvar carcinomas.